Innovation and growth: The role of labor-force qualification - Manfred Stadler (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 2003)
Endogenous innovation-based models of economic growth incorporate a scale effect predicting that larger economies grow faster and that population growth causes higher productivity growth. Recent models of semi-endogenous growth remove this scale effect but instead imply that productivity growth depends proportionally on population growth. This paper argues that an increasing qualification and not an increasing quantity of the labor force is decisive for productivity growth. The consequence of this reinterpretation of the role of the input factor labor is that growth can be enhanced by subsidizing education and hence labor-force qualification.
urn:nbn:de:bsz:21-opus-18810
Keywords: 330; Innovation; Neue Wachstumstheorie; Bildungsinvestition; Qualifikation; Bevölkerungsökonomie; Theorie; Öffentliche Bildungsausgaben; Theorie